Hearing Thresholds of a Non-noise-exposed Population in Dundee - Taylor, W. (1967)
In order to provide a control population for a previous investigation of noise-induced hearing loss in a population of female jute weavers (Taylor, Pearson, Mair, and Burns, 1965) a survey was conducted on the hearing thresholds of 296 school teachers in Dundee, Scotland, by pure tone earphone listening. This population, although not exposed to industrial noise, is subjected to city noise and differs, therefore, from the rural population of Hinchcliffe (1959), whose presbycusis data have been used in previous studies. The results show that Dundee female school teachers do not conform to British Standard in the age group 18-24 years. The presbycusis data (18-65 years age group), however, show close agreement with those of Hinchcliffe (1959) and Corso (1963). The distributions of hearing threshold observed were normal.